PENGARUH SPIRITUALITAS DAN KECERDASAN EMOSIONAL TERHADAP MINAT KEWIRAUSAHAAN YANG DIMEDIASI OLEH KREATIVITAS PADA MAHASISWA FEB USK BANDA ACEH - Sinta Melisa; Megawati Megawati (Departemen Manajemen, 2023)
This study aims to determine the effect of the Spirituality and Emotional Intelligence on Entrepreneurial Intention mediated by Creativity in students of Faculty of Economics and Business, Syiah Kuala University. The indicators discussed in the spirituality variable are 6 indicators, the indicators discussed in emotional intelligence there are 5 indicators, in the entrepreneurial intention variable there are 6 indicators, and in the creativity variable there are 4 indicators. Data was obtained through a survey of 105 people as a sample representing the research population. The data analysis method used was Statistical Product and Service Solutions (SPSS). Results The study found that the the Spirituality and Emotional Intelligence on Entrepreneurial Intention.The results also found that the creativity variable mediate between the Spirituality and Emotional Intelligence on Entrepreneurial Intention